3-Tesla T2 mapping magnetic resonance imaging for evaluation of SLAP lesions in patients with shoulder pain: an arthroscopy-controlled study - Stein, Patrick; Wünnemann, Felix; Schneider, Thomas; Zeifang, Felix; Burkholder, Iris; Weber, Marc-André; Kauczor, Hans-Ulrich; Rehnitz, Christoph (Journal of Clinical Medicine, 2023)
This study investigated the ability of T2 mapping to assess the glenoid labrum and to differentiate between healthy labral substances and superior labral anterior posterior (SLAP) lesions using arthroscopy as the gold standard. Eighteen patients (mean age: 52.4 ± 14.72 years, 12 men) with shoulder pain were examined using 3-Tesla T2 mapping. All the patients underwent shoulder arthroscopy. Using morphological sequences for correlation, regions of interest covering the entire labral substance were placed in the corresponding T2 maps. The diagnostic cutoff values, sensitivities, and specificities, as well as the inter-reader correlation coefficients (ICCs) determined by two independent radiologists, were calculated. The mean T2 value was 20.8 ± 2.4 ms for the healthy labral substances and 37.7 ± 10.63 ms in the patients with SLAP lesions. The maximum T2 value in normal labrum (21.2 ms) was lower than the minimum T2 value in the patients with SLAP lesions (27.8 ms), leading to sensitivities, specificities, and positive and negative predictive values of 100% (95% CI 54.1-100.0) for all the cutoff values between 21.2 and 27.8 ms. The ICCs ranged from 0.91 to 0.99. In summary, the data suggest that evaluation and quantification of the labral (ultra)structural integrity using T2 mapping may allow discrimination between arthroscopically confirmed SLAP lesions and a healthy glenoid labrum. T2 mapping may therefore be helpful in diagnosing patients with suspected labral damage.
Veröffentlicht: 25. April 2023
Gesehen am 24.07.2023